1999
DOI: 10.3406/reso.1999.2156
|View full text |Cite
|
Sign up to set email alerts
|

Les formats de la générosité : trois explorations du Téléthon

Abstract: Organisé depuis 1987 par une association de malades, l'Association française de lutte contre la myopathie (AFM) et une chaîne de télévision, France 2, le Téléthon réunit chaque année pendant trente heures des chercheurs, des malades, des chanteurs et le grand public dans un immense mouvement de solidarité collective qui se concrétise par un ensemble de dons qui s'élevait, lors de l'édition de 1998, à plus de 460 millions de francs. L'argent collecté lors de cette opération est destiné à financer les recherches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…(25) For discussion see Latour (1996). (26) Cardon et al (1999). is more or less indefinitely variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(25) For discussion see Latour (1996). (26) Cardon et al (1999). is more or less indefinitely variable.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, it is better understood as a process in which entities are detached from other contexts, reworked, displayed, related, manipulated, transformed, and summed in a single space. How this is done (24) Cardon et al (1999). (25) For discussion see Latour (1996).…”
Section: Resultsmentioning
confidence: 99%
“…2. Baffour Ankomah quoting BBC correspondent George Alagiah at the 'Reporting the World' Round Cardon et al (1999), pp. 39-54.…”
Section: Historical Frames and The Politics Of Humanitarian Interventmentioning
confidence: 99%
“…Finally, one cannot really understand the impact of these comments if one does not take into account the observations made on individuals placed in partly comparable situations: viewers of television programmes calling for donations. In their study of the reception of one of these programs, Cardon, Heurtin, Martin, Pharabod and Rozier (1999) showed that viewers affected by this program are motivated to act by two types of motivations. Either they feel concerned because they project themselves (as if they were the sick themselves): they then transport themselves in thought, by imagination, into the situation of the one who suffers.…”
Section: The Impact Of Websites and Social Networkmentioning
confidence: 99%